Incidental finding of mixed hemoglobinopathy in pregnant woman - Case report (Research, Society and Development, 2025)
Microcytic and hypochromic anemic syndromes, beta-thalassemia type are usually underdiagnosed. Due to the similarity of clinical manifestations, the need for complementary studies, and the lack of clinical suspicion. This hinders their timely intervention. This study aimed to show a clinical case of an incidental finding of mixed hemoglobinopathy in a pregnant woman. we present the case of a 25-year-old primigravida patient hospitalized in the context of sepsis of urinary origin, associated with encapsulated bacteria. The hemogram reports low hemoglobin and refractoriness to iron treatment. Ferrokinetic studies were normal, the blood smear revealed a varied poikilocytosis, it was suggested to perform hemoglobin electrophoresis, which reported a mixed hemoglobinopathy as an incidental finding.